Immunogenicity of one dose and two doses of adjuvanted influenza vaccine in lung transplant candidates - Valentina Polishchuk; Мikhail Kostinov; Аleksey Ryzhov; Yulia Dagil; Izabella Khrapunova; Alexander Zhestkov; Evgeny Tarabrin; Natalia Karchevskaya; Anna Vlasenko; Aristitsa Kostinova; Arseniy Poddubikov; Irina Solovieva; et al. (PLoS ONE, 2025)
Influenza is especially dangerous for high-risk patients, for whom various vaccination strategies are used to prevent this disease. This study assessed the safety and immunological effectiveness of an inactivated trivalent polymer-subunit influenza vaccine Grippol® Plus administered according to two regimens in a group of 41 patients with severe progressive bronchopulmonary disorders. It also investigated the duration of vaccine-induced antibody response in this patient population. Group 1 of the study subjects (n = 21) received one dose of Grippol® Plus, and Group 2 (n = 20) received two doses of Grippol® Plus one month apart in the same influenza season. To measure antibody levels, paired sera were tested in hemagglutination inhibition assay pre-vaccination and at months 1 and 12 post-vaccination. Vaccine immunogenicity was assessed by the Committee for Medicinal Products for Human Use (CHMP) criteria. All patients were symptom-free in the post-vaccination period. The one-dose regimen met all CHMP criteria against strains A/California/7/2009(H1N1)pdm09-like and A/Texas/50/2012(H3N2) and the criteria for seroprotection and seroconversion against the B/Massachusetts/2/2012 strain. This regimen was associated with a significant increase in Ab titers against all the three influenza viral strains. In the two-dose group, no statistically significant differences were observed in IgG Ab levels, seroprotection rate, seroconversion rate or seroconversion factor at month 1 after the first and second vaccine doses. At month 12 post-vaccination, Ab levels returned to baseline, regardless the vaccination regimen. In lung transplant candidates, one-dose vaccination with an inactivated trivalent polymer-subunit influenza vaccine was effective in generating protective antibody levels for the current influenza season.